Lenses of Legal Research: A Descriptive Essay on Legal Research Methodologies - Hari Sutra Disemadi (Fakultas Hukum, Universitas Internasional Batam, 2022)
The problem faced by researchers and scholars, especially students, is finding the right reasons for choosing legal research methods. For this reason, this article was created to make it easier for scholars to choose the right legal research method. This article is described in descriptive form using secondary data or data obtained indirectly. This article re-explains the types of doctrinal/normative and non-doctrinal/empirical legal research methods. The characteristics of legal research are included in other social science research, however, what distinguishes it is the way of thinking. Legal research must rely on gap analysis or interest analysis between legal events (das Sein) and the rule of law (das Sollen). This article also emphasizes the reasons for choosing a research method based on the 'characteristics of the research objectives'.